Human norovirus in untreated sewage and effluents from primary, secondary and tertiary treatment processes. (15th October 2016) - Campos, Carlos J.A.; Avant, Justin; Lowther, James; Till, Dale; Lees, David N.
Abstract: Wastewater treatments are considered important means to control the environmental transmission of human norovirus (NoV). Information about NoV concentrations in untreated and treated effluents, their seasonality and typical removal rates achieved by different treatment processes is required to assess the effectiveness of sewage treatment processes in reducing human exposure to NoV. This paper reports on a characterisation of concentrations of NoV (genogroups I and II) in untreated sewage (screened influent) and treated effluents from five full scale wastewater treatment works (WwTW) in England. Results are shown for effluent samples characteristic of primary- (primary settlement, storm tank overflows), secondary- (activated sludge, trickling filters, humus tanks) and tertiary (UV disinfection) treatments. NoV occurrence in untreated sewage varied between years. This variation was consistent with the annual variation of the virus in the community as indicated by outbreak laboratory reports. Significant differences were found between mean NoV concentrations in effluents subject to different levels of treatment. Primary settlement achieved approximately 1 log10 removal for both genogroups. Concentrations of NoV and Escherichia coli in untreated sewage were of the same order of magnitude of those in storm tank overflows. Of the secondary treatments studied, activated sludge was the most effective in removing NoV with mean log10 removals of 3.11 and 2.34 for GI and GII, respectively. The results of this study provide evidence that monitoring of NoV in raw sewage or treated effluents could provide early warning of an elevated risk for NoV and potentially help prevent outbreaks through environmental exposure. They also provide evidence that elimination of stormwater discharges and improvement of the efficiency of activated sludge for NoV removal would be effective for reducing the risk of environmental transmission. Graphical abstract: Highlights: High percentage (95% GI and 99% GII) of influent samples positive for NoV. Mean NoV GII levels reduced 1.5 log10 between primary and tertiary treatments. Activated sludge (MLE) reduced 3.1 and 2.3 log10 NoV GI and GII, respectively. NoV levels (GI and GII) in storm tank discharges ranged 10 1 –10 4 copies/ml. Typing NoV in raw sewage could provide early warning of NoV outbreaks.